Особливості використання засобів вербалізації концепту ALTRUISMUS в умовах інтеграційних процесів (на матеріалі німецьких публіцистичних текстів) - Черська, Жанна Борисівна (Чернівці: Рута, 2023)
Nowadays' realities dictate new manifestations of the use of components of the concept verbalization. The publicistic texts serve effectively for the objective reflection, as newspaper articles optimally record all shades of changes in social and, as a result, language processes. Taking into account the characteristics, we understand the concept as a unit of a generalized linguistic and mental resource with ethno-national or culturally determined human ideas about reality. The article analyzes the peculiarities of the verbalization means use of the concept ALTRUISM based on frequency and semantic characteristics in the modern German publicistic texts. The research material was texts of the newspaper "Die Welt" with a total sample of 30,000 word usages, within 518 examples of components, which belong to different parts of speech of the concept verbalization ALTRUISM were identified. The method of contextual analуsis of newspaper texts was used with regard to the integration social mechanisms of modern Germany. The frequency indicators of the verbalization components are interpreted within the studied sample on the basis of comparative analysis. The verbalization means analysis of the concept ALTRUISM on the material of the studied continuous sample proves the dominance of adjectives with the meaning "altruistic". It confirms the characteristics of altruistic motives, actions and goals as a manifestation of collective consciousness in German society. Mechanisms of understanding and designation of ALTRUISM in the conditions of integration processes are related to the corresponding emotional and psychological states of new society members with a migratory experience, which in linguistic expression are revealed by the use of antonyms with the meaning "selfish" to evaluate "altruistic behavior". Veiled manifestations of egoism, contextually marked by means of verbalization of the concept ALTRUISM have become a feature of the linguistic expression of social processes in modern Germany. In the future, we plan to make a comparative analysis of verbalization means of the concepts EGOISM and ALTRUISM on the material of the same sample of publicistic texts using statistical methods to establish the optimal objective characteristics of the interaction of the verbalization components, which belong to the different parts of speech.
Keywords: concept, integration processes, means of verbalization, publicistic texts, altruism